Bibliometric Analysis of Social and Environmental Innovation Research Developments: Trend Identification, Key Concepts, and Collaboration in the Scientific Literature - Dyah Palupiningtyas; Moh Gifari sono; Rival Pahrijal (Westscience Press, 2023)
A thorough bibliometric analysis is conducted in this study to investigate the state of social and environmental innovation research. The present study aims to identify developing trends, significant concepts, and collaboration networks in the subject by a thorough survey of scholarly literature. The analysis offers a comprehensive picture of the changing conversation around social and environmental innovation by incorporating a wide range of publications, such as reports, conference papers, and journal articles.The data shows a notable rise in publications over time pertaining to social and environmental innovation, indicating the field's increasing significance in tackling global issues. Research on social and environmental innovation is by its very nature interdisciplinary, incorporating elements from the social sciences, economics, business, and environmental science. This multidisciplinary approach makes it possible to fully comprehend difficult problems and come up with creative solutions. The existence of collaborative networks among scholars is highlighted by co-authorship network analysis. These networks make it easier to share knowledge, cross-pollinate concepts, and create all-encompassing solutions. The report highlights a number of topics related to emerging research, such as the role of technology in promoting social and environmental innovation, the circular economy and sustainable business models, inclusive entrepreneurship and social innovation, and sustainable supply chains. Researchers, practitioners, and policymakers can all benefit from the understanding this analysis provides. This information can be used by policymakers to guide the creation of laws that encourage environmental and social innovation. Experts are able to recognize new trends and recommended procedures. Scholars are able to pinpoint gaps in existing research and avenues for further investigation.